Effect of hydroxychloroquine on the survival of patients with systemic lupus erythematosus: data from LUMINA, a multiethnic US cohort (LUMINA L). Issue 9 (27th March 2007) - Alarcón, Graciela S; McGwin, Gerald; Bertoli, Ana M; Fessler, Barri J; Calvo-Alén, Jaime; Bastian, Holly M; Vilá, Luis M; Reveille, John D
Abstract : Objective: In patients with systemic lupus erythematosus (SLE), hydroxychloroquine prevents disease flares and damage accrual and facilitates the response to mycophenolate mofetil in those with renal involvement. A study was undertaken to determine whether hydroxychloroquine also exerts a protective effect on survival. Methods: Patients with SLE from the multiethnic LUMINA (LUpus in MInorities: NAture vs nurture) cohort were studied. A case-control study was performed within the context of this cohort in which deceased patients (cases) were matched for disease duration (within 6 months) with alive patients (controls) in a proportion of 3:1. Survival was the outcome of interest. Propensity scores were derived by logistic regression to adjust for confounding by indication as patients with SLE with milder disease manifestations are more likely to be prescribed hydroxychloroquine. A conditional logistic regression model was used to estimate the risk of death and hydroxychloroquine use with and without the propensity score as the adjustment variable. Results: There were 608 patients, of whom 61 had died (cases). Hydroxychloroquine had a protective effect on survival (OR 0.128 (95% CI 0.054 to 0.301 for hydroxychloroquine alone and OR 0.319 (95% CI 0.118 to 0.864) after adding the propensity score). As expected, the propensity score itself was also protective. Conclusions: Hydroxychloroquine, which overall is well tolerated by patients with SLE, has a protective effect on survival which is evident even after taking into consideration the factors associated with treatment decisions. This information is of importance to all clinicians involved in the care of patients with SLE.